Apparent Porosity and Compressive Strength of Heat-Treated Clay/Iron Sand/Rice Husk Ash Composites over a Range of Sintering Temperatures - Machmud, M. Nizar; Jalil, Zulkarnain; Afifuddin, Mochammad (Makara Journal of Technology, 2016)
Novel composites of clay/iron sand/rice husk ash (RHA) have been developed. Electric furnace was used to perform heat treatment on the composites to study the effect of sintering temperature on their apparent porosity and compressive strength. Two types of RHA with different bulk density were prepared to gain an understanding of the influence of apparent porosity on compressive strength of the heat-treated composites over a range of sintering temperatures. Heattreated composites, made of clay/iron sand and clay/RHA, were also prepared as a referenced material. X-ray diffraction (XRD) analysis was further performed to comprehensively discuss the role of iron sand on apparent porosity and compressive strength of the heat-treated composites. The results show that the increase of sintering temperature reduces apparent porosity of the heat-treated composites. Reducing on the apparent porosity was then followed by the increase of compressive strength of the heat-treated composites. Compressive strength of the heat-treated composites was not sensitive to the sintering temperature up to 800 °C, and it would be more improved at the sintering temperature above 800 °C. This study concludes that such sintering temperature significantly improved apparent porosity and compressive strength of the composites due to use of iron sand.